2015
DOI: 10.1039/c5ce00148j
|View full text |Cite
|
Sign up to set email alerts
|

Critical size for the β- to α-transformation in tin nanoparticles after lithium insertion and extraction

Abstract: The formation of the α-Sn phase in Sn/SnOx core/shell nanoparticles after lithium insertion and extraction was investigated for the first time and a critical size for the transformation was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Figure compares the XRD patterns of Sn film electrodes before and after 50 cycles. The pristine electrode (Figure a) shows highly crystalline β‐Sn phase with tetragonal crystal structure ( I 4 1 / amd ), consistent with that of target Sn powder, on copper metal foil. After cycling (Figure b), reflections of the β‐Sn phase are still maintained but at much reduced intensity.…”
Section: Resultssupporting
confidence: 57%
“…Figure compares the XRD patterns of Sn film electrodes before and after 50 cycles. The pristine electrode (Figure a) shows highly crystalline β‐Sn phase with tetragonal crystal structure ( I 4 1 / amd ), consistent with that of target Sn powder, on copper metal foil. After cycling (Figure b), reflections of the β‐Sn phase are still maintained but at much reduced intensity.…”
Section: Resultssupporting
confidence: 57%
“…00‐007‐0274) . After the first discharge ( D 1) to 0.6 V, while no longer peaks of Mg 2 Sn are present, new peaks at 30.6° and 32.0° attributed to (200) and (101) reflections of β‐Sn ( I 41/ amd ) metal are observed . As the first discharge capacity of 249 mAh g −1 (Figure d) determines 0.77 mole of Mg 2+ ‐ion extraction per mole of Mg 2 Sn as described above, the coexistence of Sn and Mg 2 Sn is plausible.…”
Section: Resultsmentioning
confidence: 75%
“…Generally, β to α-Sn transition can be described by Johnson-Mehl-Avrami kinetics with an Avrami exponent of 3 [7,11]. Furthermore, Oehl et al [12] reported that in nanoscale, the growth kinetics of β to α-Sn transition also depends on the size of β-Sn particles.…”
Section: Introductionmentioning
confidence: 99%